Should air travel be avoided shortly after an idiopathic sudden sensorineural hearing loss?. (31st July 2020) - Ungar, Omer J.; Shilo, Shahaf; Halevy, Nir; Cavel, Oren; Handzel, Ophir; Oron, Yahav
Abstract: Introduction : The effect of air travel on the recovery rate after idiopathic sudden sensorineural hearing loss (ISSNHL) has not been established. The advice to avoid flights is essentially based upon conjecture. Objectives : To analyze the recovery rate of patients who traveled by air shortly after they were treated for ISSNHL. Materials and methods : The hospital records of 115 newly diagnosed adult patients with unilateral ISSNHL were retrospectively collected. Included were patients who traveled by air within 90 days since the ISSNHL occurrence. The treatment protocol included oral prednisone and intratympanic dexamethasone injection when indicated. Audiograms performed upon presentation and 90 days later were compared. Results : Twelve patients were included (median age 45.5 years). The median treatment delay was 3 days. The average time from the ISSNHL to air-travel was 37 days, and the average air-travel distance was 13, 362 km. The degree of HL was moderate, moderately severe, and severe (4 patients each). Seven patients (58%) underwent full recovery. No patients experienced further deterioration of their audiometric results after air-travel. Conclusions : This study does not support the avoidance of air-travel after ISSNHL. Significance : This study is the first to investigate the effect of air-travel on ISSNHL recovery rates, a clinical question that rises commonly.